Hacia una construcción spinoziana de la imputabilidad penal: la discusión entre determinismo y libre albedrío - Mata-Quintero, Luis Enrique (2020)
In this paper we analyze, from a Spinozian perspective, the current debate between determinism and free will, in criminal imputability. To do this, we analyze the possibilities of constructing a criminal imputability concept based on the deterministic system of Spinoza’s Ethics.